2022
DOI: 10.3390/molecules27227971
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Inhibition of Quercetin on Acetylcholinesterase by Multispectroscopic and In Silico Approaches and Evaluation of Its Neuroprotective Effects on PC12 Cells

Abstract: This study investigated the inhibitory mechanism of quercetin in acetylcholinesterase (AChE) and its neuroprotective effects on β-amyloid25–35-induced oxidative stress injury in PC12 cells. Quercetin inhibited AChE in a reversible mixed manner with an IC50 of 4.59 ± 0.27 µM. The binding constant of quercetin with AChE at 25 °C was (5.52 ± 0.05) × 104 L mol−1. Hydrogen bonding and van der Waals forces were the main interactions in forming the stable quercetin–AChE complex. Computational docking revealed that qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 61 publications
(118 reference statements)
0
8
0
Order By: Relevance
“…Similarly, neuroprotection by a flavonoid quercetin has been reported in several in vitro studies (Khan et al, 2019). In a study by Liao et al (2022), quercetin showed significant AChE inhibitory activity and the double bond at positions C2 and C3 in quercetin structure played a key role in the inhibition of AChE. In another study by Kim et al (2011), gallic acid exhibited stronger AChE inhibitory effect when compared with catechin and epicatecthin.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, neuroprotection by a flavonoid quercetin has been reported in several in vitro studies (Khan et al, 2019). In a study by Liao et al (2022), quercetin showed significant AChE inhibitory activity and the double bond at positions C2 and C3 in quercetin structure played a key role in the inhibition of AChE. In another study by Kim et al (2011), gallic acid exhibited stronger AChE inhibitory effect when compared with catechin and epicatecthin.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the inner surface is composed of aromatic amino acids (Phe295, Phe338, and Tyr337). The PAS at the gorge entrance is predominantly composed of five residues: Asp74, Tyr72, Tyr124, Tyr341, and Trp286 [ 37 ]. The docked scores of 15 compounds against AChE ranged from −11.22 to −24.68 kcal/mol, compared to −14.62 kcal/mol for donepezil (co-crystal ligand) ( Table 2 and Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the stability of Aloin A binding to selected proteins, we calculated the RMSD of the skeleton atoms in the simulated trajectory. RMSD has been commonly used to estimate the degree of protein deviation from the original structure, which explains the stability of the complex [ 29 ]. As shown in Figure 7A , the plot of the HSP90AA1-Aloin A complex showed a stable equilibrium approximately after 15 ns, then a stable RMSD could be seen approximately at ~0.20 nm.…”
Section: Resultsmentioning
confidence: 99%